Implementasi Program Kampus Mengajar di Sekolah Dasar Negeri 11 Lembah Sabil Kab. Aceh Barat Daya - Putri Ashfi Raihan; Israwati Israwati; Fauzi Fauzi; M Yamin (Universitas Syiah Kuala, 2022)
The impact of the covid-19 pandemic that causes learning loss in education in Indonesia. The teaching campus is an MBKM program organized directly by the Ministry of Education and Culture and is present to help schools after the pandemic. The purpose of implementing the campus teaching program is to empower students to assist the teaching process in schools around the village/city where they live. This study aims to determine the implementation of the campus teaching program at the 11 Lembah Sabil State Elementary School and the school's response to the implementation of the teaching campus program. The approach used is a qualitative approach and the type of descriptive research. The subjects in this study were 1 principal, 6 class teachers, and students in grades V and VI. Data collection techniques in the form of semi-structured interviews and documentation. The results showed that the implementation of the campus teaching program was carried out based on consultations that had been carried out with the principal and supervising teachers without interfering with learning. The implementation time of the campus teaching program is during the learning process, interspersed with or after the learning process. The school's response to the implementation of the campus teaching program is that the school is very accepting of the campus teaching program, because it benefits and is greatly helped by the existence of this program, teachers are motivated and students experience an increase in literacy and numeracy.